Feed deprivation in Senegalese sole (Solea senegalensis Kaup, 1858) juveniles: Effects on blood plasma metabolites and free amino acid levels - Costas, B. (2014)
The effects of prolonged feed deprivation were assessed on blood plasma metabolites and free amino acid levels in Solea senegalensis. Juvenile specimens were maintained at two experimental conditions (24 h fasted and 21 days feed-deprived). In feed-deprived ﬁsh, relative growth rate and hepatosomatic index as well as plasma triglycerides and proteins levels were signiﬁcantly lower.